TET1-mediated DNA demethylation and transcription activation of MRPS17 induces lung adenocarcinoma through PI3K-AKT-mTOR pathway - Nan Zhou; Lei Song; Yang Wu; Ying Wei; Wenwen Zhang; Bingbing Wang; Yanbin Zhao; Yan Wang (Journal of Molecular Histology, 2026)
Lung adenocarcinoma (LUAD), characterized by its complex molecular heterogeneity and resistance to both conventional and targeted therapies, poses significant therapeutic challenges. Therefore, the identification of novel molecular targets is crucial for enhancing therapeutic strategies and improving patient outcomes. This study investigates the role of mitochondrial ribosomal protein S17 (MRPS17) in the progression of LUAD, with a specific focus on its interaction with the PI3K-AKT-mTOR signaling pathway. We conducted functional assays to assess cell proliferation, migration, invasion, and apoptosis in MRPS17-manipulated LUAD cell lines. Further, we explored the epigenetic regulation by TET1 through methylation analysis and investigated the downstream effects on the PI3K-AKT-mTOR pathway using Western blotting and reporter assays. Analysis revealed that MRPS17 is upregulated in LUAD tissues and is associated with a poor prognosis. In cellular models, MRPS17 overexpression was shown to promote proliferation, migration, and invasion, whereas its knockdown induced apoptosis and diminished tumorigenic capabilities both in vitro and in vivo. Importantly, TET1 was identified as a crucial regulator of MRPS17, acting through the demethylation of its promoter to enhance MRPS17 expression and subsequently activate the PI3K-AKT-mTOR pathway. MRPS17 significantly contributes to LUAD progression by enhancing tumor aggressiveness through the PI3K-AKT-mTOR pathway. The TET1-mediated demethylation of MRPS17 introduces a novel epigenetic mechanism that could be leveraged for targeted therapeutic interventions. This study not only provides foundational insights into the molecular biology of LUAD but also highlights the potential of MRPS17 as a prognostic marker and therapeutic target.